Pulmonary Toxicity Secondary to Amiodarone Use - Didar Arslan; Nagehan Aslan; Dinçer Yıldızdaş; Özden Özgür Horoz; Fadli Demir; Celal Varan (Galenos Yayinevi, 2019)
Amiodarone is an antiarrhythmic medication used for the treatment of ventricular tachycardia. In addition to unwanted effects in many tissues, one of the most important side effects of the drug is pulmonary toxicity. Toxicity may develop at any time after administration to the drug, and the risk increases depending on the dose and duration of the treatment. Clinical and laboratory findings are non-specific. In treatment, amiodarone is discontinued. In severe cases, corticosteroid therapy can be started. Here, we present the case of a patient who was followed up for two years for hypertrophic cardiomyopathy and presented to the pediatric emergency department with hemoptysis, dizziness clouding of consciousness and numb tongue. Amiodarone was used for two years to treat ventricular arrhythmia. The findings of the patient at presentation were thought to be due to amiodarone pulmonary toxicity. Amiodarone was stopped and corticosteroid therapy was initiated. Non-invasive mechanical ventilation was applied for 3 days. On the 8th day of hospitalization, the patient was transferred to the ward. The aim of this case report was to draw attention to pulmonary toxicity due to amiodarone administration.